The Relationship between Service Quality and Online Repurchase Intention in Malaysia - Teh, Kah Wai; Salim, Siti Aisyah (Research in Management of Technology and Business, 2025)
The advancement of technology and the Internet has transformed the way people interact with the digital world, enabling activities such as online communication, information searching and shopping. The Internet’s convenience and accessibility, allowing users to connect anytime and anywhere, have made it an integral part of daily life. Among these activities, online shopping has become particularly popular. However, challenges such as negative reviews, limited communication, and fraudulent sellers can significantly impact consumers’ intention to make repeat purchases online. Therefore, service quality plays an important role in consumers repurchase intention. This studies just focus on the relationship between service quality and online repurchase intention in Malaysia only. Thus, this study aims to identify the level of service quality toward online repurchase intention in Malaysia, the level of online repurchase intention in Malaysia and the relationship between service quality and online repurchase intention in Malaysia. Service quality (SERVQUAL) Model is adopted as theoretical foundation in this study. This study had surveyed 271 respondents in Malaysia. All the collected data were analysed using Statistical Package for Social Science (SPSS) to develop quantitative reports presented in the form of frequency, percentage, mean and standard deviation. This study helps service providers and online sellers to improve the service quality towards online shopping. As a result, all variables have a significant relationship with online repurchase intention. All the hypotheses were accepted in this study. Responsiveness dimension is the highest level towards online repurchase intention and reliability is the dimension with the highest correlation coefficient of 0.659.